How the Easter Egg Weevils got their spots: Phylogenomics reveals Müllerian mimicry in Pachyrhynchus (Coleoptera, Curculionidae) - Van Dam, Matthew H. (Dryad, 2022)
The evolutionary origins of mimicry in the Easter Egg weevil,
Pachyrhynchus, have fascinated researchers since first noted more than a
century ago by Alfred Russel Wallace. Müllerian mimicry, or mimicry in
which two or more distasteful species look similar, is widespread
throughout the animal kingdom. Given the varied but discrete color
patterns in Pachyrhynchus, this genus presents one of the best
opportunities to study the evolution of both perfect and imperfect
mimicry. We analyzed more than 10,000 UCE loci using a novel partitioning
strategy to resolve the relationships of closely related species in the
genus. Our results indicate that many of the mimetic color patterns
observed in sympatric species are due to convergent evolution. We suggest
that this convergence is driven by positive frequency-dependent selection.
Divergence Dating Biogeography We used MCMCTREE (Yang 2007) to perform our
divergence dating analyses. We used the topology from our ASTRAL analyses
as the starting topology for the MCMCTREE. No fossils exist for our
ingroup or near relatives, so we used a geological calibration for the
maximum age of the Philippine Islands. We used 25–30 Ma as the root node
of the Pachyrhynchini, an approximate date for the emergence of the
Philippine proto-islands proposed by Hall (2002). We used MCMCtreeR
(Puttick 2019) to estimate a normal distribution around the maximum age of
our calibration point as well as to format the tree file for MCMCTREE.
Next, we used the aforementioned tree to obtain a rough estimate of the
substitution rate using basml (Dos Reis and Yang 2013). To help accomplish
this, we randomly selected 300 loci, using many more will prevent the
analysis from completing, as well as using more data is not necessary to
approximate the uncertainty of the divergence dates (Dos Reis and Yang
2013; Zhu et al. 2015). Finally, we estimated the gradient and Hessian of
the branch lengths (Dos Reis and Yang 2011) to assist in the final
estimation of our divergence dates.
Keywords: FOS: Biological sciences; mimicry; UCE; Philippines; Biogeography; frequency-dependent selection; polymorphic; discrete traits